STRUCTURAL DESIGN OF GRAND THEATER SENEN - Lim, Terrance
Design of Grand Theater Cinema Senen includes 3 story of main cinema building on the upper structure and 2 story of basement as parking area. This final project in the field of Structural Engineering aims to design a suitable structural system for the building; and a sufficient structural element to resist different types of loads applied to the structure, including earthquake load. Structural system designed to be used on the building is special moment resisting frame with beams and columns, without shear wall, on the upper structure; and flat slab drop panel system, on the lower structure. Besides that, steel truss is used on the roof of the studio and workshop area of the building with long span void. Uniqueness of this structural design is related to the horizontal earthquake design procedure. The effect of horizontal earthquake load on structure is determined by orthogonal combination procedure on two different axis (0o-90o dan 17o -107o) as some of the building aligns with one principal axis (0o-90o) and some other aligns with another principal axis (17o -107o). One axis of two that produces the maximum response of structure will be used as reference to design sufficient structural element. The used axis is 17o -107o with response amplifier averaging on 9,776%.